886Serum folate and risk of disabling dementia: Community-based nested case-control study. (2nd September 2021) - Kishida, Rie; Yamagishi, Kazumasa; Maruyama, Koutatsu; Ikeda, Ai; Kubota, Yasuhiko; Hayama-Terada, Mina; Muraki, Isao; Shimizu, Yuji; Umesawa, Mitsumasa; Cui, Renzhe; Imano, Hironori; Sankai, Tomoko; et al.
Abstract: Background: Folate regulates homocysteine metabolism and high blood homocysteine level has been associated with risk of dementia. Accordingly, serum folate is hypothesized to decrease the risk of dementia but epidemiological evidence, especially for Japanese, is scant. The aim of this study was to examine associations between serum folate and risk of disabling dementia within a Japanese cohort over 20 years of follow-up. Methods: We performed an intracohort case-control study nested in a community-based cohort, the Circulatory Risk in Communities Study (CIRCS), involving 13934 Japanese individuals aged 40-84 years at the baseline period of 1984-2005. Serum folate was measured in 511 cases of incident disabling dementia, and in 1022 controls whose age (±1 years), sex, area, and baseline year were matched with the cases. The diagnosis of disabling dementia was performed by attending physicians under the National Long-Term Care Insurance System in Japan. Conditional odds ratios of disabling dementia according to quintiles of serum folate were calculated using conditional logistic regression models. Results: Serum folate was inversely associated with risk of disabling dementia. The multivariate odds ratios (95% confidence intervals) were 0.62(0.43-0.88), 0.71(0.49-1.00), 0.63(0.43-0.91), and 0.51(0.34-0.76) for persons with the second, third, fourth, and highest quintiles of serum folate, respectively, compared with the lowest quintiles ( P for trend = 0.19). Conclusions: Low serum folate level was associated with increased risk of disabling dementia among Japanese. Key messages: e Low folate intake may have an adverse effect on developing dementia.